2015
DOI: 10.4018/ijiit.2015070104
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bio-Inspired Approach for Multilingual Spam Filtering

Abstract: In today's digital world the email service has revolutionized the sphere of electronic communication. It has become a veritable social phenomenon in our daily life. Unfortunately, this technology has become incontestably the original source of malicious activities especially the plague called undesirable emails (SPAM) that has grown tremendously in the last few years. The battle against spam emails is extremely fierce. This paper deals with an intelligent spam filtering system called artificial heart-lungs sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Vu, uses multilanguage by introducing statistical rule-based methods to create rules for detecting in various languages [44]. Bouarara [45], uses multilanguage to detect email with learning-based methods automatically and ranks the steps to generate spam emails [47]. Contributing to our research by using the technique of collecting hoax news from the web in several different countries or languages, and produce site data effects are news hoax news from several languages including, Indonesian, English and Malaysian.…”
Section: E Multilanguage Detectionmentioning
confidence: 99%
“…Vu, uses multilanguage by introducing statistical rule-based methods to create rules for detecting in various languages [44]. Bouarara [45], uses multilanguage to detect email with learning-based methods automatically and ranks the steps to generate spam emails [47]. Contributing to our research by using the technique of collecting hoax news from the web in several different countries or languages, and produce site data effects are news hoax news from several languages including, Indonesian, English and Malaysian.…”
Section: E Multilanguage Detectionmentioning
confidence: 99%
“…Expert human translation, however, is both expensive and time-consuming. Automated translation programs, on the other hand, are efficient and cost-effective [35,36], and other research has shown encouraging results using machine learning for automated sentiment analysis for multilingual corpora [37], including spam filtering [38,39]. Given limited time and money, researchers have had to choose between greater accuracy, greater efficiency, and greater expense.…”
Section: Introductionmentioning
confidence: 99%